2016
DOI: 10.1016/j.orggeochem.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic GDGT signature for the impact of hydrothermal activity on surface deposits at the Southwest Indian Ridge

Abstract: The impact of hydrothermal activity on wider ocean geochemistry and microbial ecology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 116 publications
6
27
0
Order By: Relevance
“…It was found that there were no significant differences in microbial compositions between the hydrothermal plume samples and the ambient seawater (Li et al, ). Nevertheless, microorganisms (including bacterial and archaea) such as Fe, Mn, S oxidizers and reducers, and membrane lipids were abundant in the low‐temperature diffuse environment (Li et al, ; Pan et al, ; Peng et al, ). Therefore, organic matter from the nearby diffuse flow might be the most likely source of the ligands in Longqi hydrothermal plumes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that there were no significant differences in microbial compositions between the hydrothermal plume samples and the ambient seawater (Li et al, ). Nevertheless, microorganisms (including bacterial and archaea) such as Fe, Mn, S oxidizers and reducers, and membrane lipids were abundant in the low‐temperature diffuse environment (Li et al, ; Pan et al, ; Peng et al, ). Therefore, organic matter from the nearby diffuse flow might be the most likely source of the ligands in Longqi hydrothermal plumes.…”
Section: Resultsmentioning
confidence: 99%
“…The possible sources include diffuse flow adjacent to the high-temperature vents and/or in situ biological activities. Since the Longqi hydrothermal field was found in 2007 (Tao et al, 2012), various studies, including the physical, chemical, and biological characteristics of the hydrothermal fluids, plumes, and the diffuse flow, have been carried out (Ji et al, 2017;Li et al, 2014Li et al, , 2016Liao et al, 2016;Pan et al, 2016;Peng et al, 2011;Tao et al, 2012Tao et al, , 2014Wang et al, 2012Wang et al, , 2015. It was found that there were no significant differences in microbial compositions between the hydrothermal plume samples and the ambient seawater (Li et al, 2016).…”
Section: The Fe Speciationmentioning
confidence: 99%
“…(b) Relative contribution of sum of brGDGT‐I, brGDGT‐II, and brGDGT‐III. The sources of data are as follows: Schouten et al () and Weijers et al () for open marine sediments; Tierney et al () for lake sediments; Zell et al () for coastal sediments; Jaeschke et al () for black chimney; Pan et al () for low‐temperature hydrothermal deposits; Weijers et al () for soils; He et al () for hot springs; and Liu et al () for seawater column. GDGT = glycerol dialkyl glycerol tetraether.…”
Section: Discussionmentioning
confidence: 99%
“…There are also relatively few studies on the effects of hydrothermal activity on the surrounding environment, especially the metalliferous sediments (Pan et al, 2016) formed via a combination of sulfide mass wasting and debris flow, low-temperature fluid flow and mineralization, or plume formation, dispersal and fallout (Dias et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These three distinct surface deposits provide an opportunity to explore the potential effects of hydrothermal activity on the surrounding sediments. Our previous study examining the distribution of glycerol dialkyl (and monoalkyl) glycerol tetraether (GDGT and GMGT) archaeal membrane lipids (Pan et al, 2016) clearly showed that GDGT distributions in normal marine sediments, near-field metalliferous sediments and low-temperature hydrothermal deposits vary significantly, whereas the far-field metalliferous sediments have the same GDGT distribution as that of the background sediments.…”
Section: Introductionmentioning
confidence: 99%